PENGARUH PEMBELAJARAN TEAM ASSISTED INDIVIDUALIZATION (TAI) BERBANTUAN MEDIA SMART AND INTERESTING CARD (SIC) TERHADAP HASIL BELAJAR SISWA (Jurnal Inovasi Pendidikan Kimia, 2013)
This experiment aimed to determine the influence of student’s learning outcomes of Senior High School (SHS) in Parakan through the application of TAI (Team Assisted Individualization) assisted of SIC (Smart and Interesting Card) media on the subject of redox reaction. The population in this experiment were X grade students Senior High School (SHS) in Parakan of the school year 2011/2012. Determination of the sample used cluster random sampling system that obtained two classes where X-3 as an experimental group that was treated by using TAI method assisted by SIC media and X-4 as a control group that was treated conventional methods. The research data was obtained by the method of documentation, testing, questionnaire and observation. The final analysis methods are normalization test, the similarity of two varians test, difference of two average test, gain test, biserial correlation, determination coefficient and analysis of questionnaire and observation sheet. The results showed that experiment class better than the control class. The results of study obtained results of the experimental group had an average 76,78 and a control group had an average of 67,82. TAI method assisted by SIC media give contribution to the learning outcome as 30%.Key words: TAI learning, SIC media